PERCOBAAN PENYULINGAN KAYU CENDANA (Santalum album L.) DARI KUPANG - Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1988)
Cendana  oil,  an  essential  oil  extracted   from Santalum  album  L. is  an  important non  wood  forest  products from Indonesia. Recently,  there  has been a lot  of  inquiries  on  the  quality  of  the  oil obtained  from different part  of a tree and on  the effect  of processing condition on  oil properties.In  this study,  the  Santalum  album L. wood  was obtained  from  Kupang, Nusa Tenggara Timur province  of Indonesia, where  this  wood  is   native  to. The  wood  samples  were prepared  for  further  processing  in two different  sizes being those retained on and screened  out  wood  particles  of  40  mesh screen. The sample  specimens were  taken  from trunk and root parts, then  treated  in three processing  times.  The yield and the chemical properties  of the oil were measurea and recorded. A gas chromatography was employed  in determining the  santalol   content   of  the  oil  and  the  result  was analysed  and evaluated.